2012
DOI: 10.1261/rna.028506.111
|View full text |Cite
|
Sign up to set email alerts
|

La-motif–dependent mRNA association with Slf1 promotes copper detoxification in yeast

Abstract: The La-motif (LAM) is an ancient and ubiquitous RNA-binding domain defining a superfamily of proteins, which comprises the genuine La proteins and La-related proteins (LARPs). In contrast to La, which binds and stabilizes pre-tRNAs and other RNA polymerase III transcripts, data on function and RNA targets of the LARPs have remained scarce. We have undertaken a global approach to elucidate the previously suggested role of the yeast LARP Slf1p in copper homeostasis. By applying RNA-binding protein immunopurifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 80 publications
1
50
0
1
Order By: Relevance
“…Taken together, these results strongly suggested roles for Puf3p in the biogenesis and function of mitochondrial proteins. Indeed, later studies confi rmed the roles of Puf3p in mitochondrial function and in the localization of mRNAs (70) . Over-expression of Slf1p renders cells resistant to elevated copper concentrations in the medium, and this effect is dependent on the interaction of Slf1 with target mRNAs.…”
Section: Coordination -Organization Of Functionally Related Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results strongly suggested roles for Puf3p in the biogenesis and function of mitochondrial proteins. Indeed, later studies confi rmed the roles of Puf3p in mitochondrial function and in the localization of mRNAs (70) . Over-expression of Slf1p renders cells resistant to elevated copper concentrations in the medium, and this effect is dependent on the interaction of Slf1 with target mRNAs.…”
Section: Coordination -Organization Of Functionally Related Messagesmentioning
confidence: 99%
“…Over-expression of Slf1p renders cells resistant to elevated copper concentrations in the medium, and this effect is dependent on the interaction of Slf1 with target mRNAs. From this, we deduced that Slf1p regulates a copper regulon, thus allowing cells to adapt to elevated copper concentrations (70) . Such a mode of regulation would be analogous to a previously identifi ed yeast RBP network triggering coordinated responses to iron defi ciency (71) .…”
Section: Coordination -Organization Of Functionally Related Messagesmentioning
confidence: 99%
“…It is thought that the specific complement of RBPs bound to a given mRNA specifies its post-transcriptional fate, but nearly all existing data are limited to defining pairwise interactions between a single RBP and a single mRNA species. Previous work to identify the mRNA targets bound by individual RBPs has mostly relied on purification of the RBP from a whole-cell lysate followed by analysis of the copurifying mRNAs (Gerber et al 2004;Ule et al 2005;Keene 2007a,b;Hogan et al 2008;Bohnsack et al 2009;Granneman et al 2009Granneman et al , 2010Wolf et al 2010;Scherrer et al 2011;Schenk et al 2012). These approaches do not differentiate between two RBPs that bind simultaneously to their common mRNA targets and two RBPs that bind to a common set of mRNA targets but at different times or in different cellular locations.…”
mentioning
confidence: 99%
“…Slf1 has been previously shown to be involved in mRNA-specific regulation of translation in response to oxidative stress and to facilitate the translation of stress-responsive mRNAs (Kershaw et al, 2015), whereas Sbp1 is an abundant RBP found in stress granules and P-bodies implicated in translational repression (Mitchell et al, 2013; Segal et al, 2006). It has been also shown that overexpression of Slf1 increases mitochondrial respiration and leads to yeast chronological lifespan extension (Chatenay-Lapointe and Shadel, 2011), and in addition protects cells from copper-induced oxidative stress (Schenk et al, 2012). Consistent with activation of Slf1 in the tor1Δ mutant, cells lacking TOR1 demonstrated increased copper resistance compared to wild-type cells (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%